2008
DOI: 10.1021/cg701145q
|View full text |Cite
|
Sign up to set email alerts
|

Shape-Controlled Synthesis and Assembly of Copper Sulfide Nanoparticles

Abstract: Cu 2 S nanocrystals and superlattices were synthesized by a simple solution-phase thermolysis of the copper dodecanethiolate polymer precursor. X-ray diffraction (XRD), selected area electron diffraction (SAED), and high resolution transmission electron microscopy (HRTEM) confirmed the chalcocite crystal structure of the nanocrystals. Monodispersed Cu 2 S nanodisks, spheres and hexagon nanoplates could be fabricated with this method. Further, copper sulfide nanoarrays assembled by nanoparticles of different sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…Cu 2 S nanodisks, spheres, and hexagonal nanoplates were assembled into superstructures through this method. They believed that the assembled structures are closely related to the lamellar structure of the copper thiolate precursor ( 319 ).…”
Section: Assembly Of Anisotropic Nanostructuresmentioning
confidence: 99%
“…Cu 2 S nanodisks, spheres, and hexagonal nanoplates were assembled into superstructures through this method. They believed that the assembled structures are closely related to the lamellar structure of the copper thiolate precursor ( 319 ).…”
Section: Assembly Of Anisotropic Nanostructuresmentioning
confidence: 99%
“…In particular, Cu 2 S, a p ‐type semiconductor with a bandgap of 1.2–2.0 eV, is of great interest due to its potential applications in solar cells,2–4 biosensors,4 and the photodegradation of organic pollutants 5. In the past few years, various Cu 2 S nanostructures including nanospheres,6 nanodisks,7–10 nanorods,11 nanowires,12 and nanoribbons13 have been prepared. Very few reports have demonstrated the formation of hollow Cu 2 S nanostructures, yet their surfaces are generally rough 14, 15.…”
Section: Introductionmentioning
confidence: 99%
“…18 Long anisotropic superstructures have been observed in solutions of the same nanoparticles by a different group. 19 In a previous study, we have shown that the stacking of CdSe nanoplatelets in solution can have important consequences on their emission properties. Indeed, the interaction between the nanoplatelets within a stack induces the appearance of a phonon-replica line in their emission spectrum at low temperature.…”
mentioning
confidence: 99%